Flow Through Porous Media Induced by an Impervious Rotating Disk in the Presence of Magnetic Field - SHARMA, P.K.; CHAUDHARY, R.C. (Engineering Transactions, 2005)
The flow of an electrically conducting viscous incompressible fluid, due to an infinite impervious rotating disk bounded by porous medium is discussed. It is assumed that the flow between the disk and the porous medium is governed by Navier-Stokes equations and that in the porous medium – by Brinkman equations. A uniform magnetic field is applied in the direction normal to flow. At the interface (porous medium – clear fluid boundary), a modified set of boundary conditions is applied. Analytical expressions for the velocity and shearing stress are calculated and effects of various parameters upon them are examined.